A Precise Description Of The Economic Responsibility Of The Department Of Purchases And Storehouses According To The Concepts Of Effectiveness And Efficiency: A New Initiative To Enrich The Thought Of CSR - Younis A. Battal Saleh (International Journal of Economics Development Research (IJEDR), 2022)
This study aims to identify and describe the economic responsibility of PWD, based on the concepts of effectiveness and efficiency. Method: To determine and describe the economic responsibilities of the departments that make up the FOS in any corporation, the concepts of effectiveness and efficiency in accomplishing the tasks assigned to those departments were chosen, taking into account the criteria for evaluating the level of quality of effectiveness and efficiency. Result: Through the concepts of effectiveness and efficiency in completing tasks, this study was able to determine and describe the economic responsibility for PWD that was chosen to be the subject of this study, as follows: Providing the tangible and intangible needs for other departments included in the corporation’s FOS in a timely manner, with the specified specifications and at the lowest possible cost.Originality/Value: The idea of this study, which depends on the concepts of effectiveness and efficiency in performing tasks, can be adopted in defining and describing the economic responsibilities of the departments included in the FOS of any for-profit corporation. The economic responsibility of the departments lies in the extent of their commitment to the standards of effectiveness and efficiency in the performance of the tasks assigned to them. This study is an enrichment of the thought of CSR and it will be considered the starting point for many studies and research in this field. Keywords: Corporate Social Responsibility. Economic Responsibility. Effectiveness and Efficiency. Functional Organizational Structure.  Purchasing and Warehouse Department.